Response of the Stabilization of Organic Carbon to Straw Incorporation and Nitrogen Application: Evidence from Carbon Fractions and Bacterial Survival Strategies - Shenglin Liu; Xiaodong Ding; Zeqiang Sun; Zhaohui Liu; Runxiang Du; Zhichang Jing; Shirong Zhang (Agronomy, 2025)
Despite the global imperative to enhance carbon sequestration in agricultural landscapes, saline–alkali soils present distinctive soil–microbe constraints that limit our understanding of optimal management strategies. This study addresses critical knowledge gaps regarding the mechanistic relationships between bacterial community structure and carbon stabilization processes in saline–alkali soil. A three-year field experiment was conducted in the Yellow River Delta, China, with two N levels (N1, 270 kg N ha−1; N2, 210 kg N ha−1) and three C treatments (S0, 0 kg C ha−1; S1, 5000 kg C ha−1; S2, 10,000 kg C ha−1). SOC sequestration by straw incorporation increased by 16.34–22.86% and 8.18–11.91%, with no significant difference between the S1 and S2 treatments, because the specific C mineralization rate (SCMR) of the S2 treatment was 13.80–41.61% higher than the S1 treatment. The reduced nitrogen application (N2) enhanced SOC sequestration efficiency by 3.40–12.97% compared with conventional rates, particularly when combined with half straw incorporation. Furthermore, compared with the N1S1 treatment, the N2S1 treatment induced qualitative transformations in carbon chemistry, increasing aromatic carbon compounds (28.79%) while reducing carboxylic fractions (10.06%), resulting in enhanced structural stability of sequestered carbon. Bacterial community analysis revealed distinctive shifts in bacterial composition under different treatments. Half straw incorporation (S1) increased the abundance of oligotrophic strategists (Verrucomicrobiae and Acidimicrobiia) while decreasing copiotrophic bacteria (Bacteroidia), indicating a transition from r-strategy to k-strategy microbial communities that fundamentally altered carbon cycling. Half straw incorporation and reduced N application were beneficial to stabilize SOC composition, reduce mineralization rates, optimize bacterial survival strategy, and thus achieve SOC sequestration.